Deregulated Expression of miR-224 and its Target Gene: CD59 Predicts Outcome of Diffuse Large B-cell Lymphoma Patients Treated with R-CHOP - Song, Guoqi; Song, Guorong; Ni, Huiyun; Gu, Ling; Liu, Hong; Chen, Baoan; He, Bangshun; Pan, Yuqin; Wang, Shukui; C. Cho, William (Current Cancer Drug Targets, 2014)
miRNAs are non-coding RNA molecules; their deregulations may contribute to cancer pathogenesis. However, the mechanisms of how miRNA dysfunction contributes to the lymphomagenesis of diffuse large B-cell lymphoma (DLBCL) are not well established. In this study, we analyzed the expression of miR-224 in four DLBCL cell lines and 168 patients’ specimens. We found that the expression of miR-224 in DLBCL was down-regulated compared with normal B-cell but was not statistically different between the germinal center B-cell-like-type and the activated B-cell-like-type. Using bioinformatics prediction and luciferase report assays, we demonstrated that miR-224 directly down-regulated CD59 expression by binding to its 3’-untranslated region. We also used immunohistochemical staining of CD59 in human DLBCL specimens and analyzed the relationship between the expression of miR-224, CD59 and the overall/progress-free survival of DLBCL patients who were uniformly treated with rituximab,cyclophosphamide, adriamycin, vincristine, and prednisone (R-CHOP). We found that miR-224 may contribute to DLBCL pathogenesis. Most importantly, the expression of miR-224 and CD59 can predict the response and outcome of DLBCL patients treated with R-CHOP.
Keywords: CD59